Uniformity evaluation method for duplex smelting titanium alloy cast ingot

By using a multi-dimensional sampling method in EBCHM+VAR dual-melted titanium alloy round ingot, the length direction and circular cross-section component content are obtained, and the component fluctuation value is calculated, the problem of difficult to evaluate component uniformity in the prior art is solved, and a more comprehensive and objective uniformity evaluation of titanium alloy ingot is achieved.

CN119738544APending Publication Date: 2025-04-01XIANYANG TIANCHENG TITANIUM IND

Patent Information

Application Number
CN202411592370.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

It is difficult for the prior art to comprehensively evaluate the composition uniformity of EBCHM+VAR double-smelted titanium alloy round ingots, especially in ingots with large diameters and long lengths, with fewer sampling points, which makes it difficult to grasp the composition situation.

Method used

The multi-dimensional sampling method is adopted, including the detection of component content in different dimensions of the length direction and circular cross-section. Through the steps of peeling, sawing and cross-section sampling, the nominal element components of titanium alloys at multiple sampling points are obtained, and the component fluctuation value is calculated to evaluate uniformity.

Benefits of technology

A more comprehensive and objective evaluation of the composition uniformity of the entire titanium alloy ingot is achieved, and the stability of the ingot composition can be more intuitively judged, providing a clearer process optimization direction and application reference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119738544A_ABST
    Figure CN119738544A_ABST
Patent Text Reader

Abstract

The invention relates to a uniformity evaluation method for a duplex smelting titanium alloy cast ingot. Comprising the following steps: peeling a finished product cast ingot of duplex smelting titanium alloy, sampling in the length direction of the finished product cast ingot, sawing the finished product cast ingot, sampling the sawing section of the finished product cast ingot, and detecting the nominal element composition of the titanium alloy at a plurality of sampling points. And the nominal composition fluctuation values of the titanium alloy in the length direction and the cross section are obtained through calculation, and then the uniformity evaluation of the titanium alloy is obtained. According to the method, the content of components in different dimensions in the length direction and the circular cross section is detected, and data analysis is performed, so that the component condition of the whole duplex smelting titanium alloy cast ingot can be more comprehensively known, chemical component uniformity evaluation can be performed on component fluctuation through data analysis, and the stability of the components of the cast ingot can be more comprehensively and intuitively judged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of uniformity evaluation of refractory alloys. Background Art

[0002] At present, the traditional titanium alloy smelting method still mainly relies on secondary and above vacuum arc remelting (VAR). Although this technology is relatively mature, it has limitations in reducing costs and meeting new requirements for sustainable development. Low-cost and high-quality smelting with added return materials through the dual smelting method of electron beam cold hearth melting (EBCHM) and vacuum arc remelting has become an effective way to make full use of the process advantages to achieve the purity and uniformity of the smelting products with added return materials.

[0003] For VAR smelting, which is a relatively mature technology, the existing sampling method usually only samples the circumference of the ingot in the length direction, and mainly focuses on the head and tail points. Although this method can basically meet the needs of VAR smelting ingots, due to the high saturated vapor pressure elements in the EBCHM smelting process are prone to fluctuations, it is difficult to fully grasp the composition uniformity of the entire ingot of EBCHM+VAR dual smelting when there are fewer sampling points. That is, due to the lack of relevant sampling methods for the cross section of the round ingot in the existing technology, the data obtained by the existing technology alone cannot grasp the composition of the entire ingot, especially the EBCHM+VAR dual smelting titanium alloy round ingot with a large diameter and a long length. Summary of the invention

[0004] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a method for evaluating the uniformity of a double-melting titanium alloy ingot for EBCHM+VAR, especially a round titanium ingot or round billet with a large diameter and a long length, for sampling different dimensions of the double-melting titanium alloy ingot, thereby realizing the uniformity evaluation of the double-melting titanium alloy round ingot.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for evaluating the uniformity of a double-melting titanium alloy ingot, comprising the following steps:

[0006] Step 1: peeling the finished ingot of smelted titanium alloy;

[0007] Step 2: Sampling along the length of the finished ingot:

[0008] In the length direction of the finished ingot after peeling, starting from 100 to 250 mm at the head of the finished ingot, every 300 to 600 mm is used as a sampling point, and the surface sample of the finished ingot is taken, and the element detection is performed, so as to obtain the nominal element composition of the titanium alloy at multiple sampling points in the length direction of the finished ingot;

[0009] Step 3: Sawing of finished ingots:

[0010] After peeling, the riser depth of the finished ingot is increased by 30 to 50 mm to perform sawing processing to obtain the head sawing sample of the finished ingot;

[0011] The tail sawing sample with a length of 30 to 50 mm at the tail of the finished ingot after peeling;

[0012] At the midpoint of the length direction of the finished ingot after peeling in the middle section, 10±2mm to the left and right, saw a 20±2mm thick middle sawn sample;

[0013] Step 4: Sampling of the finished ingot cross section:

[0014] On the sawn sample cross sections at the head, tail and middle, take chip samples at the center of the cross section, then take multiple chip samples on at least two straight lines vertically intersecting at the center, and the sampling interval on the same straight line is less than or equal to 150 mm, and perform element detection, that is, obtain the nominal element composition of the titanium alloy at multiple sampling points on the cross section of the finished ingot;

[0015] Step 5: According to the nominal element composition of the titanium alloy at multiple sampling points, the nominal composition fluctuation values ​​in the length direction and in the cross section of the titanium alloy are calculated respectively, and then the uniformity evaluation of the titanium alloy is obtained.

[0016] Furthermore, the cutting speed of the peeling treatment is 3-5r / min, the feed rate is 0.4-0.6mm / r, the number of cutting times is 1-2 times, and the first cutting depth is 2-3mm, so that there are no residual cold shut, interlayer, and loose defects on the side surface of the finished ingot after peeling. At the same time, the head of the finished ingot with a length of 200-300mm is fine-turned, and the roughness Ra≤6.3μm is used for riser depth detection.

[0017] Furthermore, the step 2 is specifically as follows: in the length direction of the finished ingot after peeling, starting from 100 to 250 mm from the head of the finished ingot, sampling points are taken every 300 to 600 mm until the sampling point reaches a position 100 to 250 mm away from the tail of the finished ingot; when the distance from the last sampling point to the tail is greater than or equal to 350 mm, sampling is taken again at a distance of 100 to 150 mm from the tail.

[0018] Furthermore, the surface samples described in step 2 include chip samples and block samples.

[0019] Furthermore, in step 4, a drill is used to take samples at different positions of the cross section, and before sampling, the sawn sample cross sections at the head, tail and middle of the finished ingot and the sampling drill are wiped clean with alcohol.

[0020] Furthermore, the calculation formula of the relative fluctuation value of the nominal component in step 5 is:

[0021]

[0022] Where: x1, x2, x3, ..., x n The element contents detected at multiple sampling points along the length direction and on the cross section of the finished ingot;

[0023] is the average value of the element content at the sampling points.

[0024] Furthermore, the finished ingot is a double-melted finished ingot obtained by at least one melting in an electron beam cooling furnace and then remelting in a vacuum arc consumable furnace.

[0025] Furthermore, the finished ingot is a round titanium ingot or round billet. After peeling, a finished ingot with a diameter of 500-1000 mm is obtained, and the diameter of the finished ingot before peeling is 520-1020 mm and the length is greater than 3 m.

[0026] Furthermore, the finished ingot is a round titanium ingot or round billet, and the center point of the cross section described in step 4 is the center point of the cross section of the finished ingot.

[0027] The beneficial effects of the present invention are as follows: the present invention proposes a uniformity evaluation method for EBCHM+VAR dual-melting titanium alloy ingots, which objectively evaluates the chemical composition uniformity of the entire ingot by detecting the component content in different dimensions of the length direction and the circular cross section and performing data analysis. The present invention can not only more comprehensively understand the composition of the entire ingot, but also evaluate the component fluctuations through data analysis, thereby more comprehensively and intuitively judging the stability of the ingot composition. This method more effectively determines the sampling points and their numbers of electron beam cooling beds and vacuum arc dual-melting titanium alloy ingots, providing clearer guidance and reference for subsequent process optimization directions and ingot applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the sampling positions in the length direction of the chemical composition of the present invention;

[0029] Figure 2 The ingot sawing method of the present invention and the marked schematic diagram;

[0030] Figure 3 This is a schematic diagram of the sampling position of the circular cross section of the chemical composition of the present invention;

[0031] Figure 4 This is a physical picture of the chemical composition sampling of a circular cross section of a specific example of the present invention;

[0032] Figure 5 This is a physical picture of the chemical composition sampling of the circular cross section of the specific example of the present invention. DETAILED DESCRIPTION

[0033] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0034] In order to achieve the above object, the present invention provides the following specific implementation methods:

[0035] Example 1: Figure 2 , Figure 3 As shown, a method for evaluating the uniformity of a double-melting titanium alloy ingot comprises the following steps:

[0036] Step 1: Peel the finished ingot of smelted titanium alloy:

[0037] The finished ingot is obtained by melting at least once in an electron beam cooling furnace and then remelting in a vacuum arc consumable furnace;

[0038] The cutting speed of the peeling treatment is 3-5r / min, the feed rate is 0.4-0.6mm / r, the number of cutting times is 1-2 times, and the first cutting depth is 2-3mm, so that there are no residual cold shut, interlayer, and loose defects on the side surface of the finished ingot after peeling. At the same time, the head of the finished ingot with a length of 200-300mm is finish-turned, and the roughness Ra≤6.3μm is used for riser depth detection.

[0039] Step 2: Sampling along the length of the finished ingot:

[0040] In the length direction of the finished ingot after peeling, starting from 100 to 250 mm at the head of the finished ingot, every 300 to 600 mm is used as a sampling point, and the surface samples of the finished ingot are taken. The surface samples include chip samples and block samples, and element detection is performed to obtain the nominal element composition of the titanium alloy at multiple sampling points in the length direction of the finished ingot;

[0041] Step 3: Sawing of finished ingots:

[0042] like Figure 2 As shown, the riser depth of the finished ingot after peeling is increased by 30 to 50 mm to perform sawing processing, and the head sawing sample of the finished ingot is obtained;

[0043] The tail sawing sample with a length of 30 to 50 mm at the tail of the finished ingot after peeling;

[0044] At the midpoint of the length direction of the finished ingot after peeling in the middle section, 10±2mm to the left and right, saw a 20±2mm thick middle sawn sample;

[0045] Step 4: Sampling of the finished ingot cross section:

[0046] like Figure 3 As shown, on the sawn sample cross sections of the head, tail and middle, a chip sample is taken at the center point of the cross section, and then multiple chip samples are taken on at least two straight lines vertically intersecting at the center point, and the sampling interval on the same straight line is less than or equal to 150 mm, and element detection is performed, that is, the nominal element composition of the titanium alloy at multiple sampling points on the cross section of the finished ingot is obtained;

[0047] A drill bit is used to take samples at different positions of the cross section, and before sampling, the sawn sample cross sections at the head, tail and middle of the finished ingot and the sampling drill bit are wiped clean with alcohol.

[0048] Step 5: According to the nominal element composition of the titanium alloy at multiple sampling points, the nominal composition fluctuation values ​​in the length direction and the cross section of the titanium alloy are calculated respectively, and then the uniformity evaluation of the titanium alloy is obtained.

[0049] The calculation formula for the relative volatility of the nominal component is:

[0050]

[0051] Where: x1, x2, x3, ..., x n The element contents detected at multiple sampling points along the length direction and on the cross section of the finished ingot;

[0052] is the average value of the element content at the sampling points.

[0053] Example 2: Figure 1 As shown, it is the same as Example 1, except that the step 2 is to start from 100 to 250 mm from the head of the finished ingot in the length direction of the finished ingot after peeling, and take sampling points every 500 mm until the sampling point reaches a position 100 to 250 mm away from the tail of the finished ingot; when the distance from the last sampling point to the tail is greater than or equal to 350 mm, sampling is taken again at a distance of 100 to 150 mm from the tail.

[0054] Example 3: The same as Example 1, except that the finished ingot is a round titanium ingot or round billet, and after the peeling process, a finished ingot with a diameter of 500-1000 mm is obtained, and the finished ingot before the peeling process has a diameter of 520-1020 mm and a length greater than 3 m. The center point of the cross section described in step 4 is the center of the cross section of the finished ingot.

[0055] Example 4: The same as Example 2, except that the finished ingot is a round titanium ingot or round billet, and after the peeling process, a finished ingot with a diameter of 500-1000 mm is obtained, and the finished ingot before the peeling process has a diameter of 520-1020 mm and a length greater than 3 m. The center point of the cross section described in step 4 is the center of the cross section of the finished ingot.

[0056] In order to further illustrate the technical scheme and technical effects of the present invention, the following examples are provided:

[0057] Specific example 1: Take the finished TA15 titanium alloy ingot with a melting crucible diameter of φ720mm as an example, the ingot length is 3800mm.

[0058] Step 1: Peel the φ720mm finished ingot. The first cut is 2-3mm deep. The second cut is adjusted according to the distribution of oxide scale and defects on the surface of the ingot. After peeling, the ingot diameter is φ700mm.

[0059] Step 2: Sampling in the length direction is required to start from 150mm from the head of the ingot, and chip samples are taken every 500mm, namely: 150mm, 650mm, 1150mm, 1650mm, 2150mm, 2650mm, 3150mm, 3650mm.

[0060] Step 3: After peeling, saw the head of the finished ingot to the depth of the riser + 30mm; saw the tail to 30mm. The remaining ingot is sawed 10mm to the left and right of the midpoint in the length direction. The sawing method of the 20mm disc is as follows: Figure 2 shown.

[0061] Step 4: Drill chip samples on the discs at the head, middle and tail of the ingot. When sampling, wipe the sample surface and the sampling drill bit with alcohol. The sampling points of a single original piece are determined according to the ingot shape. The sampling spacing in the same direction should be ≤150mm, specifically 1 at the center of the circle, 4 evenly divided "cross" points with a radius of 150mm for the ingot, 4 evenly divided "cross" points with a radius of 300mm for the ingot, 9 points for sampling on a single disc, and the circular cross section sampling as follows: Figure 4 shown.

[0062] Step 5: The sample test items in the length direction of the ingot and the circular cross section of the ingot are the nominal composition of TA15, namely Al, V, Mo, Zr, as shown in Table 1 and Table 2:

[0063] Table 1 Element composition of Al, V, Mo and Zr in the length direction / %

[0064] Position / mm 150 650 1150 1650 2150 2650 3150 3650 Al(%) 6.84 6.85 6.69 6.60 6.83 6.82 6.83 6.96 V(%) 2.34 2.36 2.33 2.39 2.34 2.32 2.31 2.30 Mo(%) 1.79 1.79 1.79 1.77 1.78 1.77 1.77 1.77 Zr(%) 2.34 2.35 2.28 2.40 2.34 2.29 2.33 2.33

[0065] Table 2 Al and V element composition in cross section direction / %

[0066]

[0067] Step 6: According to the nominal composition in the length direction and the circular cross-section direction, as shown in Table 2 and Table 3 respectively, according to the formula, it can be calculated that the composition fluctuations of Al, V, Mo and Zr elements in the length direction of this TA15 alloy ingot are 1.16%, 0.91%, 0.49% and 1.07% respectively, and the fluctuation values ​​of the circular cross-section are 2.08%, 1.12%, 1.73% and 1.75% respectively.

[0068] Step 7: According to the calculated length direction and circular section nominal composition fluctuation values, combined with Table 3, it can be seen that the composition of this TA15 titanium alloy ingot belongs to level 2, and the composition uniformity is good.

[0069] Table 3 Alloy element composition fluctuation level table

[0070]

[0071] Specific Experimental Example 2: Taking the finished TC4 titanium alloy ingot with a melting crucible diameter of φ820 mm as an example, the ingot length is 3500 mm.

[0072] Step 1: Peel the φ820mm finished ingot. The first cut is 2-3mm deep. The second cut is adjusted according to the distribution of oxide scale and defects on the surface of the ingot. The ingot diameter after peeling is φ795mm.

[0073] Step 2: Sampling in the length direction is required to start from 250mm from the head of the ingot, and chip samples are taken every 500mm, namely: 250mm, 750mm, 1250mm, 1750mm, 2250mm, 2750mm, 3250mm.

[0074] Step 3: After peeling, saw the head of the finished ingot to the depth of the riser + 50mm; saw the tail to 50mm. The remaining ingot is sawed 10mm to the left and right of the midpoint in the length direction to 20mm round pieces. The sawing method is as follows Figure 2 shown.

[0075] Step 4: Drill chip samples on the discs at the head, middle and tail of the ingot. When sampling, wipe the sample surface and the sampling drill bit with alcohol. The sampling points of a single original piece are determined according to the ingot shape. The sampling spacing in the same direction should be ≤150mm, specifically 1 at the center of the circle, 4 evenly divided "cross" points with a radius of 120mm, 4 evenly divided "cross" points with a radius of 240mm, and 4 evenly divided "cross" points with a radius of 360mm. A single disc is sampled at 13 points, and the circular cross section sampling is as follows: Figure 5 shown.

[0076] Step 5: The sample testing items in the length direction of the ingot and the circular cross-section of the ingot are the nominal composition of TC4, i.e. Al and V.

[0077] Table 4 Al and V element composition in the length direction / %

[0078] Position / mm 250 750 1250 1750 2250 2750 3250 Al(%) 6.40 6.44 6.38 6.29 6.20 6.21 6.24 V(%) 4.27 4.14 4.18 4.18 4.18 4.19 4.18

[0079] Table 5 Al and V element composition in circular cross section direction / %

[0080]

[0081] Step 6: According to the nominal compositions in the length direction and the circular cross-section direction as shown in Table 4 and Table 5, respectively, according to the formula, it can be calculated that the composition fluctuations of Al and V elements in the length direction of this TC4 alloy ingot are 1.33% and 0.57% respectively, and the fluctuation values ​​of the circular cross-section are 1.82% and 0.57% respectively.

[0082] Step 7: According to the calculated length direction and circular section nominal composition fluctuation values, combined with Table 1, it can be seen that the composition of this TC4 titanium alloy ingot belongs to level 1, and the composition uniformity is good.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for evaluating the uniformity of a double-melting titanium alloy ingot, characterized in that: The following steps are involved: Step 1: peeling the finished ingot of smelted titanium alloy; Step 2: Sampling along the length of the finished ingot: In the length direction of the finished ingot after peeling, starting from 100 to 250 mm at the head of the finished ingot, every 300 to 600 mm is used as a sampling point, and the surface sample of the finished ingot is taken, and the element detection is performed, so as to obtain the nominal element composition of the titanium alloy at multiple sampling points in the length direction of the finished ingot; Step 3: Sawing of finished ingots: After peeling, the riser depth of the finished ingot is increased by 30 to 50 mm to perform sawing processing to obtain the head sawing sample of the finished ingot; The tail sawing sample with a length of 30 to 50 mm at the tail of the finished ingot after peeling; At the midpoint of the length direction of the finished ingot after peeling in the middle section, 10±2mm to the left and right, saw a 20±2mm thick middle sawn sample; Step 4: Sampling of the finished ingot cross section: On the sawn sample cross sections at the head, tail and middle, take chip samples at the center of the cross section, then take multiple chip samples on at least two straight lines vertically intersecting at the center, and the sampling interval on the same straight line is less than or equal to 150 mm, and perform element detection, that is, obtain the nominal element composition of the titanium alloy at multiple sampling points on the cross section of the finished ingot; Step 5: According to the nominal element composition of the titanium alloy at multiple sampling points, the nominal composition fluctuation values ​​in the length direction and in the cross section of the titanium alloy are calculated respectively, and then the uniformity evaluation of the titanium alloy is obtained.

2. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 1, characterized in that: The cutting speed of the peeling treatment is 3-5r / min, the feed rate is 0.4-0.6mm / r, the number of cutting times is 1-2 times, and the first cutting depth is 2-3mm, so that there are no residual cold shut, interlayer, and loose defects on the side surface of the finished ingot after peeling. At the same time, the head of the finished ingot with a length of 200-300mm is fine-turned, and the roughness Ra≤6.3μm is used for riser depth detection.

3. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 1, characterized in that: The step 2 is specifically as follows: starting from 100 to 250 mm from the head of the finished ingot, sampling points are taken every 300 to 600 mm in the length direction of the finished ingot after peeling, until the sampling point reaches a position 100 to 250 mm from the tail of the finished ingot; when the distance from the last sampling point to the tail is greater than or equal to 350 mm, sampling is taken again at a distance of 100 to 150 mm from the tail.

4. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 1, wherein: The surface samples described in step 2 include chip samples and block samples.

5. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 1, characterized in that: In the step 4, a drill is used to take samples at different positions of the cross section, and before sampling, the sawn sample cross sections at the head, tail and middle of the finished ingot and the sampling drill are cleaned with alcohol.

6. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 1, characterized in that: The calculation formula of the relative fluctuation value of the nominal component in step 5 is: Where: x1, x2, x3, ..., x n The element contents detected at multiple sampling points along the length direction and on the cross section of the finished ingot; is the average value of the element content at the sampling points.

7. The method for evaluating uniformity of a double-melting titanium alloy ingot according to any one of claims 1 to 6, characterized in that: The finished ingot is a double-melted finished ingot that is melted at least once in an electron beam cooling furnace and then remelted in a vacuum arc consumable furnace.

8. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 7, characterized in that: The finished ingot is a round titanium ingot or round billet. After peeling, a finished ingot with a diameter of 500-1000mm is obtained. The diameter of the finished ingot before peeling is 520-1020mm and the length is greater than 3m.

9. The method for evaluating uniformity of a double-melting titanium alloy ingot according to claim 7, characterized in that: The finished ingot is a round titanium ingot or round billet, and the cross-sectional center point described in step 4 is the cross-sectional center of the finished ingot.

Citation Information

Patent Citations

  • Preparation method for titanium alloy TC18 through vacuum smelting

    CN102644006A

  • EB furnace and VAR furnace duplex smelting method for titanium alloy ingot casting

    CN115537589A

  • Sampling segregation evaluation method for EB furnace titanium alloy return scrap smelting round ingot and application

    CN117848757A

Cited By

  • Sampling segregation evaluation method for EB furnace titanium alloy return scrap smelting round ingot and application

    CN117848757A